Relative Cost, Profitability and Efficiency among Different Types of Dairy Farms at Bharatpur, Chitwan, Nepal - Dhakal, Shiva Chandra (Agriculture Development Journal, 2022)
Dairy sector is gradually commercializing and modernizing with the use of improved breeds, processed feeds, cultivated grass, fodders, medicines and additives in Nepal. In this context, this study was designed to evaluate the relative cost, return, resource use efficiency, return to scale and profitability of milk production in different type of dairy farms. Primary data were collected through face-to-face interview using semi-structured interview schedule from a sample of 240 dairy farms selected from simple random sampling technique in 8 wards of Bharatpur Metropolitan City, Chitwan. Data were analyzed using descriptive statistics, cost and profit analysis, linear production function and Cobb-Douglas function. It was found that pure buffalo farms were facing negative profit margin against the profit of Rs. 32565 and Rs. 106627 at cow and mix system of dairy farming, respectively. Average variable cost of per liter milk production was Rs. 93.70, Rs. 54.80 and Rs. 44.73 for buffalo, cow and mix farms, respectively with benefit-cost ratio of 0.99, 1.44 and 1.62 for respective categories of the farms. Green grass, dry fodder, labour, feed, medicines and additives were significantly contributing to milk production in buffalo and cow farms. But, only grass, fodder and labour were contributing to milk production in mix dairy farms. All categories of farms were suffering from decreasing return to scale but they were still profitable over variable cost. Labour was the most contributing factor in all three categories of farms and thus dairy farming seems potential to create productive employment. This is concluded that dairy farming system can be promoted profitably by enhancing the level of use of labour, grass, fodder, medicines and additives.